Revascularization for acute blunt popliteal artery injury. Issue 3 (22nd December 2015) - Nishimura, Kengo; Hamasaki, Takafumi; Ohno, Takashi; Nishihara, Akihiko; Ito, Hisao; Ishiguro, Shingo
Abstract : Case: A 45‐year‐old man was brought to our hospital in pre‐shock after falling from a motorcycle. As we diagnosed him with open fracture of the right femur with leg ischemia, we performed revascularization of injured popliteal artery and treated the leg. The pathological findings showed fragmentation and decrease of elastic fibers and fragmentation of collagen fibers, but no inflammatory cells or intimal hyperplasia, and no dissection. Outcome: Unfortunately, amputation had to be carried out on the 29th postoperative day due to infection and leg dysfunction. The postoperative course was uneventful. The patient could walk with an artificial leg and was discharged approximately 5 months after popliteal artery replacement. Conclusions: We report a case of revascularization involving a patient with open fracture of the right femur due to acute blunt popliteal artery injury.